Exploring a natural fiber extracted from henequen plant leaves: A sustainable innovation for reinforcement in composite materials - Thandavamoorthy Raja (Results in Engineering)
This research investigates the potential of a novel fiber extracted from Henequen plant leaves as a sustainable reinforcement for composite materials. Henequen fibers, rich in cellulose and lignin, offer an eco-friendly alternative to synthetic fibers. The fibers were analysed for their structural, mechanical, and functional properties. XRD analysis showed a crystallinity index of 42.4 %, indicating a high degree of crystallinity, which contributes to their strength. FTIR spectra revealed characteristic peaks at 3335 cm⁻¹ (OH stretching), 2900 cm⁻¹ (CH stretching), and 1730 cm⁻¹ (CO stretching), confirming the presence of cellulose, hemicellulose, and lignin. Single fiber tensile testing revealed a tensile strength of 21.07 MPa and a tensile modulus of 8.2 GPa, demonstrating the fibers' potential for high-performance applications. SEM analysis revealed a rough surface morphology, which enhances fiber-matrix adhesion in composites. TGA results indicated thermal stability up to 350 °C, while UV spectroscopy showed effective UV absorption, particularly in the 270–280 nm range. Antibacterial tests revealed inhibition zones of 31 mm against E. coli, demonstrating the fibers’ antibacterial properties. These findings highlight Henequen fibers as a sustainable and high-potential material for composite reinforcement.